Oil palm biomass powder and method for producing the same, and biomass composite molded article and method for producing the same - Hassan, Mohd Ali; Ariffin, Hidayah; Ahamad Nordin, Noor Ida Amalina; Nishida, Haruo; Ando, Yoshito; Nagata, Hirokazu; Shirai, Yoshihito; Karuppuchamy, Subbian (2014)
Provided are oil palm biomass powder preferable as a homogeneous industrial fiber material, and a composite shaped article with excellent mechanical properties, which comprises the oil palm biomass powder.The oil palm biomass powder has no peak in the temperature range of 180°C to 320°C but has a peak in the temperature range of 300°C to 400°C in a differential thermogravimetric curve, and 50% by mass or more of the oil palm biomass powder is in the major axis range of 1°C to 500°C. The biomass composite shaped article is produced by molding a composition comprising biomass powder and a thermoplastic resin or a thermo setting resin prepolymer at a mass ratio of 5:95 to 80:20.